Association of first trimester serum level of placental growth factor (PlGF) and cervical length with onset of preterm labour - Sahoo, Ipsita; Dey, Madhusudan; A., Jayamol (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preterm labour (PTL) or premature labour is defined as one where labour starts before the 37th completed week. The incidence of preterm birth is around 5-10% and it is the leading cause of perinatal morbidity and mortality. Diagnosis and treatment of PTL is challenging. However, owing to the availability of effective strategies for prevention of preterm birth, risk identification and early prediction is even more essential. This may provide opportunity for intervention and better obstetric care. Various biochemical markers were studied for prediction of preterm labour, but the sensitivity and specificity were found to be low. This study focuses on determining whether serum level of PlGF and ultrasound measure of cervical length at 10 – 14 weeks period of gestation can be used for early prediction of preterm labour. Methods: 296 antenatal women participated in this prospective observational study carried out from Dec 2015 to Sep 2017 at a tertiary care hospital. Serum level of PlGF was determined at 10-14 weeks. In the same sitting, cervical length was measured by transvaginal sonography. All these patients were followed up in antenatal OPD for monitoring the onset of preterm labour. Results: Incidence of preterm labour was 6.76 %. Maternal characteristics and obstetric factors were comparable in cases and controls. Serum PlGF level and cervical length values were lower in preterm labour group than term deliveries. But this result was not statistically significant. Conclusions: Lower levels of PlGF and cervical length were seen in preterm labour group, although it was not found to be statistically significant.